Net zero by 2050: Investigating carbon-budget compliant retrofit measures for the English housing stock. (June 2022) - Li, X.; Arbabi, H.; Bennett, G.; Oreszczyn, T.; Densley Tingley, D.
Abstract: The UK has enacted one of the most ambitious carbon reduction targets striving for net zero emissions by 2050. A major challenge to achieving this is decarbonizing heating demand with almost 25 m homes in need of retrofit. This paper explores a range of retrofit interventions to the English residential stock. These are deployed immediately in 2021 to investigate the maximum carbon reduction that could be achieved. The impact of these interventions on embodied and operational carbon emissions is estimated from 2021 to 2050. The resulting emissions are compared to estimated national carbon budgets, in order to ascertain, if, and with what combination of retrofit measures, the English housing stock can stay within carbon budgets. The results show that mass deployment of air source or ground source heat pumps can reliably achieve combined embodied and operational emissions within national carbon budgets by 2050. The careful selection of insulation materials is key in bringing down the embodied emissions, particularly to meet stricter carbon budgets. The identified scale and pace of deployment thus needed to stay within carbon budgets is likely to pose enormous practical challenges. To overcome these challenges, we argue for (a) urgently increasing both heat pump deployment, and renewable generation targets beyond existing pledges, (b) increasing social awareness of residential retrofit benefits, and (c) providing more attractive financing options to incentivise and facilitate retrofit uptake. Highlights: Exploration of retrofit measures to meet carbon budget for English housing stock. Whole life carbon analysis including both embodied and operational carbon emissions. Carbon payback for all measures except PV estimated to be within 5 years. CCC Carbon budget only met with rapid deployment of air/ground source heat pumps. Meeting Tyndall carbon budget also requires wall insulation using low carbon materials.